Congenital long QT syndrome caused by a KCNH2 pathogenic variant exhibiting “motor seizures”: a case report and literature review - Mei Jin; Fan Yang; Yakun Du; Libo Zhao; Xueran Zhao; Jing Liu; Jing Zhang; Suzhen Sun (BMC Pediatrics)
Abstract A retrospective analysis was conducted to evaluate the clinical characteristics, diagnostic challenges, and management strategies in a child with congenital long QT syndrome (cLQTS) caused by a KCNH2 gene pathogenic variant presenting as “motor seizures”. The case involved a 10-year-old boy with a two-year history of recurrent loss of consciousness, which had worsened during the preceding week. Clinical manifestations included sudden episodes of unconsciousness, rightward strabismus of both eyes, cyanosis of the lips, guttural vocalizations, rigidity and shaking of the upper limbs, and urinary incontinence. These events typically lasted approximately two minutes, initially occurring semiannually but escalating to daily episodes over the past week, affecting both awake and sleep states. Video electroencephalography (VEEG) showed generalized slow waves and low voltage activity, while electrocardiography (ECG) demonstrated QTc prolongation, paired, and multi-source ventricular ectopy preceding torsades de pointes. Genetic testing identified a pathogenic c.1697G > A mutation in the KCNH2 gene corroborating the clinical diagnosis of cLQTS. Following confirmation, the patient was initiated on long-term oral therapy with propranolol and nicorandil. Under this regimen, the patient was seizure-free for 7-month. For patients with seizures or seizure-like episodes, such as extremity movement or rigidity, it is necessary to perform an ECG examination. Additionally, dynamic ECG and electrolyte assessments should be conducted when necessary to minimize the risk of misdiagnosis and inappropriate treatment. When VEEG shows a “slow-flat-slow” pattern, differentiation from A-S syndrome caused by malignant arrhythmias is critical. Once cLQTS is diagnosed, it is imperative to initiate prompt and aggressive treatment to mitigate the risks of syncope and sudden cardiac death.